2021
DOI: 10.21203/rs.3.rs-447551/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antiviral Bioactivity of Resveratrol Against Zika Virus Infection in Human Retinal Pigment Epithelial Cells

Abstract: Resveratrol (RES) is a polyphenol with increasing interest for its inhibitory effects on a wide variety of viruses. Zika virus (ZIKV) is an arbovirus of the Flaviviridae family for which there is no approved treatment or vaccine, and which has become a major global health threat. Within the broad spectrum of ophthalmological manifestations after infection, retinal pigment epithelial cells (RPE) type is one of the most permissive and susceptible to the virus. This work explored the protective effects of RES on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Indeed, viruses use host-specific factors to complete their multiplication cycles, and inhibition of mitochondrial enzymes involved in nucleoside biosynthesis has been shown to be an effective antiviral strategy. In conclusion, they demonstrated the efficacy of resveratrol as an antiviral agent in the treatment of Zika-virus-induced eye diseases [50]. A schematic representation of the mechanism of action of resveratrol, proposed by the authors [50], is shown in Figure 8.…”
Section: Mechanism Of Action Of Resveratrol In the Treatment Of Zika ...mentioning
confidence: 89%
See 1 more Smart Citation
“…Indeed, viruses use host-specific factors to complete their multiplication cycles, and inhibition of mitochondrial enzymes involved in nucleoside biosynthesis has been shown to be an effective antiviral strategy. In conclusion, they demonstrated the efficacy of resveratrol as an antiviral agent in the treatment of Zika-virus-induced eye diseases [50]. A schematic representation of the mechanism of action of resveratrol, proposed by the authors [50], is shown in Figure 8.…”
Section: Mechanism Of Action Of Resveratrol In the Treatment Of Zika ...mentioning
confidence: 89%
“…In conclusion, they demonstrated the efficacy of resveratrol as an antiviral agent in the treatment of Zika-virus-induced eye diseases [50]. A schematic representation of the mechanism of action of resveratrol, proposed by the authors [50], is shown in Figure 8.…”
Section: Mechanism Of Action Of Resveratrol In the Treatment Of Zika ...mentioning
confidence: 89%
“…Notably, a study proved the protective effects of resveratrol on ZIKV-infected human RPE cells. Also, a study reported that resveratrol had a high affinity for two enzymes of the rate-limiting steps of pyrimidine and purine biosynthesis and viral polymerase [92]. Currently, the inhibition of resveratrol on the NS3 helicase of Zika virus has been demonstrated.…”
Section: Effects Ofmentioning
confidence: 99%